2022
DOI: 10.3390/foods11030469
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of a Novel Soy Protein Isolate-Sugar Beet Pectin Emulsion Gel and Its Application as a Multi-Phased Nutrient Carrier

Abstract: Emulsion gel, a novel oral delivery carrier, provides the possibility to co-load hydrophilic and lipophilic nutrients simultaneously. In this study, duo-induction methods of laccase and glucono-δ-lactone (L&GDL) or laccase and transglutaminase (L&MTG) were used to prepare the soy protein isolate-sugar beet pectin (SPI-SBP) emulsion gel. The textural data of the emulsion gel was normalized to analyze the effect of different induction methods on the gel property of the SPI-SBP emulsion gels. The characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 41 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Additionally, as the mass ratio of BW reached 8.0%, most of the oil droplets coalesced and formed “banded” structures, and the typical “bubble in bubble” structure of the double emulsions was lost. Probably, higher content of beeswax led to higher viscosity of primary emulsion, the inhomogeneous secondary emulsification caused the aggregation of oil droplets [ 14 , 24 ]. Besides, the large size and poor fluidity of droplets might also lead to the coalescence of adjacent droplets during microscopic observation, and thus the formation of irregular “banded” structures.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, as the mass ratio of BW reached 8.0%, most of the oil droplets coalesced and formed “banded” structures, and the typical “bubble in bubble” structure of the double emulsions was lost. Probably, higher content of beeswax led to higher viscosity of primary emulsion, the inhomogeneous secondary emulsification caused the aggregation of oil droplets [ 14 , 24 ]. Besides, the large size and poor fluidity of droplets might also lead to the coalescence of adjacent droplets during microscopic observation, and thus the formation of irregular “banded” structures.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al . (2022b) prepared a soy protein isolate‐beet pectin (SPI‐SBP) emulsion gel and indicated that emulsion gel is a novel oral drug carrier that can simultaneously load hydrophilic and lipophilic nutrients. In simulated digestion experiments, the gel network induced by different methods regulated the release of β‐carotene and riboflavin in the SPI‐SBP emulsion gel.…”
Section: The Applications Of Glycoprotein Conjugates In the Food And ...mentioning
confidence: 99%
“…Additionally, these original parameter data can be normalized to one-dimensional data based on Minkowski distance. Zhang et al [102] have normalized the three-dimensional data (hardness, springiness, and cohesiveness) into one-dimensional data, which is defined as a comprehensive property index (CPI). This CPI reflected the overall texture properties of the emulsion gel material and was used for further discussion in the relationship between textures and gelation induction methods of emulsion gel.…”
Section: Texturementioning
confidence: 99%
“…Scanning electron microscopy (SEM) uses a focused electron beam to scan the sample surface, producing high-resolution images by detecting secondary electrons emitted from the sample. This technique can provide more detailed information about the network structure of emulsion gels, such as pore size and distribution, wall thickness, and oil droplet distribution [40,95,102]. Freeze drying is a common method for sample dehydration.…”
Section: Microscopymentioning
confidence: 99%